2018
DOI: 10.1021/acsaem.8b01239
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework-Derived Sea-Cucumber-like FeS2@C Nanorods with Outstanding Pseudocapacitive Na-Ion Storage Properties

Abstract: Sodium-ion batteries (SIBs) are supposed to be attractive energy strorage and supply devices due to the abundant reserves of sodium. Their limited specific capacity and rate capacity, however, are standing in the way of the extensive application of SIBs. It is reported herein that porous sea-cucumber-like FeS 2 @C nanorods can act as efficient cathode materials to satisfy the rigorous requirements of the proposed applications. The fabrication of the sea-cucumber-like FeS 2 @C nanorods involves the hydrothermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…Figure b shows the Fe 2p XPS spectrum of FeS 2 /NPCF. It can be seen that through fitting, two signal peaks were located at 719.5 and 707.9 eV, which were related to Fe 2p 1/2 and Fe 2p 3/2 , while the peaks at 711.0 and 724.7 eV correspond to the Fe–O bond. It is related to the slight oxidation of FeS 2 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Figure b shows the Fe 2p XPS spectrum of FeS 2 /NPCF. It can be seen that through fitting, two signal peaks were located at 719.5 and 707.9 eV, which were related to Fe 2p 1/2 and Fe 2p 3/2 , while the peaks at 711.0 and 724.7 eV correspond to the Fe–O bond. It is related to the slight oxidation of FeS 2 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…[10] MoS 2 , VS 2 , TiS 2 and NiS 2, SnS and FeS 2 have been widely studied as 2D anode material. [11][12][13][14] Mortazavi et al [15] reported that the layered MoS 2 could be used as the anode material for SIBs, which has a maximum theoretical capacity of 146 mAh g À 1 . DFT calculations prove that the NiS 2 surface has a high chemical affinity towards Na ions, promising the concentration of Na ion on the surface for fast redox reactions during sodiation/de-sodiation of NiS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the obtained materials usually exhibit a carbon coating with uneven thickness and weak bonding between the TMS and the carbon layer, which is unfavorable for charge-transfer applications and cannot totally guarantee the prevention of volume changes during the charge/discharge process. [20][21][22] Recently, it was reported that a simple one-step synthesis of Ni 3 S 2 nanowires through low-temperature pyrolysis of sulfonic acid group-containing resin with Ni foam. 23 Although some carbon species were also generated with the Ni 3 S 2 nanowires, the obtained carbon could not be uniformly covered on the surface of nanowires.…”
Section: Introductionmentioning
confidence: 99%